Body Composition in Children and Adolescents Residing in Southern Europe: Prevalence of Overweight and Obesity According to Different International References - López-Sánchez, Guillermo Felipe; Sgroi, Maurizio; D’Ottavio, Stefano; Díaz-Suárez, Arturo; González-Víllora, Sixto; Veronese, Nicola; Smith, Lee (Frontiers in Physiology, 2019)
The objective was to analyze body composition in children and adolescents of Southern Europe, studying prevalence of overweight and obesity. This investigation involved 512 girls and 488 boys between 7-to 19-years old. Variables evaluated were Body Mass Index (BMI) and Fat Mass (FM; electrical bioimpedance). The references used to establish the prevalence according to BMI were those of the World Health Organization (WHO) and the International Obesity Task Force (IOTF); in the case of FM, the Child Growth Foundation (CGF) reference. There were significant differences (p<0.05) in the prevalence of overweight and obesity between the three classifications (32.3% according to IOTF, 37.3% according to WHO and 39.8% according to CGF), being higher in males. WHO-IOTF concordance was substantial (kappa=0.793), whereas concordances WHO-CGF (kappa=0.504) and IOTF-CGF (kappa=0.447) were moderate. The authors recommend evaluating overweight and obesity not only with BMI, but also with FM, and always specify the references used.